Conformable Sturm-Liouville Problem with Modified Coulomb Potential - Ozarslan, Ramazan; Najemadeen, Isam (My University, 2020)
In this paper, Conformable derivative order version of the Sturm-Liouville problem having modified Coulomb potential is obtained. The studied system proves the shape of the conformable derivative general statement of the Sturm-Liouville operator with boundary conditions. Furthermore, real of eigenvalues and ??-orthogonal of eigenfunctions have been proved for the problem considered. Additionally, the representation of the solution of the Sturm-Liouville problem having modified Coulomb potential is found. The results are shown comparativelyby figures.
Keywords: Matematik; Fizik; Matematik